Good prospects for green energy in Romania - Mariana Papatulica; Petre Prisecaru (Global Economic Observer)
EU has to attain the strategic objectives for 2020: 20% of energy from renewable sources, cutting the emissions of greenhouse gases by 20% and diminishing the dependence on imported fuels, that is why in the last years European Commission has decided that MS should increase the flexibility of programs to promote green energy and cut subsidies. Although wind and solar energy have become more competitive in terms of cost in the last two decades, many production technologies need to be improved, also storage and transport capacities. Romania has an important potential of renewable energy resources and has introduced a functional mechanism for supporting their development based on a system of mandatory quotas for electricity, combined with trading a number of green certificates, but all the costs are transferred to the consumers.This system may carry an overcompensation for the investors and also an excessive burden on the consumers. Most investments were made in wind and hydro, the fewest in solar and biomass. Market liberalization may create more competition and stimulate the investments in different renewable resources.